Simulation of the Finite-Difference Time-Domain (FDTD) Method in 2-Dimensional Electromagnetic Wave Propagation in Absorption Media - Muh Fachrul Latief; Idawati Supu (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
This research reviewed Maxwell’s equations and Numerical Discretization using the Finite Difference Time Dependent (FDTD) method. First, Maxwell’s equations are introduced in a linear dielectric medium for 1-dimensional and 2-dimensional configurations, which are built based on the polarization between Transverse-Magnetic (TM) and Transverse-Electric (TE). Then, it presented the frequency-dependent absorption boundary conditions for the electromagnetic field equations used in that configuration. In addition, the correlation between the variation of the grid with respect to the x-axis and y-axis, as well as the variation of the dielectric constant of the medium on the propagation of electromagnetic waves, has been studied in this paper. A numerical result provides an excellent accuration and approximation in establishing boundary conditions for wave spacing in adsorbed media at 1-dimensional and 2-dimensional configurations